International Experience with Private Sector Participation in Power Grids : Peru Case Study - World Bank Group (World Bank, Washington, DC, 2016)
This case study is part of an analytical effort aimed at advising World Bank staff and country clients on options for private sector participation (PSP) in transmission and distribution. The report is based on data collected on the Peruvian case, the review of literature, as well as on a set of interviews held with power sector agencies, including the regulator and system operator, power sector companies and experts in the field. The problems of the power sector were linked to its structure, a legal framework that guaranteed a public monopoly and the use on subsidies as a political tool to redistribute income and control inflation. The crisis justified measures in line with a thorough neoliberal economic reform that was underway. This reform included the reduction of an oversized public sector and the unbundling and privatization of the power sector. The privatization of transmission was justified on the grounds of attracting fresh capital and achieving greater efficiency. PSP in distribution was justified on the same grounds, plus another important factor, it was seen also as a way to prevent or minimize government interference on the day‐to‐day operations of utilities and, most important, to avoid the politicization of electricity tariffs.